Study on Reactivity of Circulating Fluidized Bed Combustion Fly Ashes in the Presence of Water - Salain I.M.A.K. (Civil Engineering Dimension, 2010)
A study on reactivity of four different Circulating Fluidized Bed Combustion (CFBC) fly ashes has been realized in the presence of water. Paste of each ash was prepared and analyzed for its setting time, expansion and strength. The products of hydration, and their evolutions over a period of time were identified by X-ray diffraction and differential thermal analysis. The results of this study show that the reactivity of the CFBC fly ashes is strongly related to their chemical composition, essentially to their quantity of silica, alumina, lime and sulfate, which promote principally the formation of ettringite, gypsum and C-S-H. It is further noted that the intensity and the proportion of these phases determine the hydration behavior of the CFBC fly ashes.